Analiza hybrydowych tekstów Unii Europejskiej — wybrane zagadnienia metodologiczne - Brom, Przemysław (Przekłady Literatur Słowiańskich, 2014)
Analysis of the hybryd texts of the European Union — se.lected methodological aspects Multilingual European community requires certain efficient translation methods. Translation can be simplified by standardization of texts, but then the texts resulting from the translation process seem to be somewhat “inadequate” for the target culture. These texts, often described as “hybrid”, weren’t broadly analysed before. This paper presents a possible methodology for conducting such an analysis. Key words: hybrid texts, translation in the EU, methodology